Aberrant DNA Methylation in Hereditary Non-Polyposis Colorectal Cancer without Mismatch Repair Deficiency - Goel, Ajay (2010)
BACKGROUND & AIMS: Approximately half of the families that fulfill Amsterdam criteria for Lynch syndrome or hereditary non-polyposis colorectal cancer (HNPCC) do not have evidence of the germline mismatch repair (MMR) gene mutations that define this syndrome and result in microsatellite instability. The carcinogenic pathways and the best diagnostic approaches to detect microsatellite stable (MSS) HNPCC tumors are unclear. We investigated the contribution of epigenetic alterations to development of MSS HNPCC tumors. METHODS: Colorectal cancers were divided in four groups: 1. Microsatellite stable, Amsterdam positive (MSS HNPCC) (N=22); 2. Lynch syndrome cancers (identified mismatch repair mutations) (N=21); 3. Sporadic MSS (N=92); 4. Sporadic MSI (N=46). Methylation status was evaluated for CACNAG1, SOCS1, RUNX3, NEUROG1, MLH1, and LINE-1. KRAS and BRAF mutations status was analyzed. RESULTS: MSS HNPCC tumors displayed a significantly lower degree of LINE-1 methylation, marker for global methylation, than any other group. Whereas most MSS HNPCC tumors had some degree of CpG island methylation, none presented a high index of methylation. MSS HNPCC tumors had KRAS mutations exclusively in codon 12, but none harbored V600E BRAF mutations. CONCLUSIONS: Tumors from Amsterdam-positive patients without mismatch repair deficiency (MSS HNPCC) have certain molecular features, including global hypomethylation that distinguish them from all other colorectal cancers. These characteristics could have an important impact on tumor behavior or treatment response. Studies are underway to further assess the cause and effects of these features.